Homecomings returning POWs and the legacies of defeat in postwar Germany - Biess, Frank (Princeton, N.J. : Princeton University Press, 2006)
This book focuses on one of the most visible and important consequences of total defeat in postwar Germany: the return to East and West Germany of the two million German soldiers and POWs who spent an extended period in Soviet captivity. These former prisoners made up a unique segment of German society. They were both soldiers in the war of racial annihilation on the Eastern front and then suffered extensive hardship and deprivation themselves as prisoners of war. The book examines the lingering consequences of the soldiers' return and explores returnees' own responses to a radically changed and divided homeland. Historian Frank Biess traces the origins of the postwar period to the last years of the war, when ordinary Germans began to face the prospect of impending defeat. He then demonstrates parallel East and West German efforts to overcome the German loss by transforming returning POWs into ideal post-totalitarian or antifascist citizens. By exploring returnees' troubled adjustment to the more private spheres of the workplace and the family, the book stresses the limitations of these East and West German attempts to move beyond the war. Based on a wide array of primary and secondary sources, Homecomings combines the political history of reconstruction with the social history of returnees and the cultural history of war memories and gender identities. It unearths important structural and functional similarities between German postwar societies, which remained infused with the aftereffects of unprecedented violence, loss, and mass death long after the war was over.
Impending defeat: military losses, the Wehrmacht and ordinary Germans -- Confronting defeat: returning POWs and the politics of victimization -- Embodied defeat: medicine, psychiatry, and the trauma of the returned POW -- Survivors of totalitarianism: returning POWs and the making of West German citizens -- Antifascist conversions: returning POWs and the making of East German citizens -- Parallel exclusions: the West German POW trials and the East German purges -- Absent presence: missing POWs and MIAs -- Divided reunion: the return of the last POWs -- Histories of the aftermath.
Includes bibliographical references (p. [307]-357) and index.
JSTOR
Keywords: Sovetskaja Associacija Meždunarodnogo Prava; Ex-prisoners of war -- Germany -- History -- 20th century; World War, 1939-1945 -- Prisoners and prisons; Germany -- History -- 1945-1955.; Ex-prisonniers de guerre -- Allemagne -- Histoire -- 20e siècle.; Guerre mondiale, 1939-1945 -- Prisonniers et prisons; Allemagne -- Histoire -- 1945-1955.; HISTORY / Military / World War II; Ex-prisoners of war; Prisoners of war; Germany; Deutscher Kriegsgefangener; Geschichtsbild; Heimkehr; Heimkehrer; Kriegsgefangener; Soziale Integration; Weltkrieg; Deutschland; Rückkehr; Sowjetunion; Deutschland; Krijgsgevangenen; Tweede Wereldoorlog; Terugkeer; Duitsland; DDR; Germany -- History -- 1945-1955.; Ex-prisoners of war -- Germany; World War, 1939-1945 -- Prisoners and prisons, German; Anciens prisonniers de guerre -- Allemagne -- 1945- ...; Guerre mondiale (1939-1945) -- Prisonniers et prisons; Allemagne -- 1945-1955.; Andra världskriget 1939-1945 -- krigsfångar -- Tyskland; 1900-1999; History